Gadis Crispy Chocojar Enterprise / Arina Dahlia Zahiruddin ... [et al.] - Zahiruddin, Arina Dahlia; Kamarudin, Marsya Maisarah; Mohd Shahrim, Nur Dania Farisha Shaikh; Mohd Misran, Nur Qurratu Anisah; Norman, Nurul Fatihah; Hamzah, Siti Nurul Ain (2022)
The name given for our company is GADIS CRISPY CHOCOJAR Enterprise which represents all of our group members that consist of 6 girls. Gadis Enterprise is a small business that sells local products which are crispy choco jars based on chocolates and cereal. This is a company that is actively established by partnership that supplies food. Our companies concentrate on the production of the food to provide excellent outcomes for our customers by supplying them our products according to demand. We started our business on a small scale as a starter because we only have a premise for processing the product and carrying out management activities. Our business was mainly run at Batu Pahat, Johor. officially this business were started on 1st January 2022. The reason why we choose this business is because it is one of the products that are highly requested and popular among local people. So it will be easy for us to attract the customers by doing some variations into the products. Besides, we want to serve the customers simple but high quality products that are easy to bring anywhere without worrying the tub will break. We hope that in the upcoming 2 or 3 years, this business will be able to sustain and survive. We want to help many individuals who want to generate incomes and grow their experiences in running business. Next, we also want to make our heart desires come true by opening a branch that completes with production equipment to offer more job opportunities for local people.